2022
DOI: 10.58917/ijpe.v1i2.19
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Gaya Belajar terhadap Hasil Belajar Fisika Siswa

Abstract: Studi ini merupakan penelitian ex-post facto pada bulan Maret-April Tahun Ajaran 2020/2021 di SMAN 9 Pinrang dengan tujuan untuk mengetahui pengaruh gaya belajar terhadap hasil belajar fisika siswa Kelas XI SMAN 9 Pinrang. Varibel gaya belajar diukur menggunakan angket. Sedangkan variabel hasil belajar fisika datanya dikumpulkan menggunakan instrumen dokumen. Dari hasil penelitian diperoleh: 1) Gaya belajar yang dominan di Kelas XI SAN 9 Pinrang adalah gaya belajar visual yaitu sebesar 44%, kemudian gaya belaj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…The results of this study are in line with research that has been conducted by Nurnaifah et al (2022) that there is a positive and significant influence of visual learning styles on physics learning outcomes. In addition, it is also in line with research conducted by Darmawati (2017) which states that an increase in learning styles affects learning achievement.…”
Section: Quality Analysis Of Video Grading Rubricsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of this study are in line with research that has been conducted by Nurnaifah et al (2022) that there is a positive and significant influence of visual learning styles on physics learning outcomes. In addition, it is also in line with research conducted by Darmawati (2017) which states that an increase in learning styles affects learning achievement.…”
Section: Quality Analysis Of Video Grading Rubricsupporting
confidence: 90%
“…Teachers should recognize that students have diverse and distinct learning needs in classrooms that implement differentiated learning. This is supported by research conducted by Nurnaifah et al (2022), which found a positive and significant influence of visual learning style on physics learning outcomes.…”
Section: Introductionsupporting
confidence: 55%
“…Research by Astuti et al, (2023) differences in math learning and. While in research (Nurnaifah et al, 2022) has differences in mathematics learning. While in this study student learning outcomes, while in previous studies had variable X visual, auditory, and kinesthetic learning styles and took science.…”
Section: Resultsmentioning
confidence: 98%
“…The weak correlation between learning styles and student learning outcomes can be attributed to various factors, including teachers, students, and research errors. According to Nurnaifah, there are additional factors that exert an influence on the association between learning styles and learning outcomes (Nurnaifah 2022). These factors encompass learning resources, learning environment, learning media, interests, and motivation.…”
Section: Resultsmentioning
confidence: 99%